Cost and Demand Elements in the Inflationary Process - Pitchford, J. D. (Review of Economic Studies, 1957)
In order to describe an inflationary process it is necessary to have some knowledge of how prices and wages are determined. Conventional economic theory has regarded prices (and wages) as reacting to the level of excess demand or supply in the commodity (labour) market. Investigations have shown, however, that especially in manufacturing industries prices are often determined by applying a profit margin to variable costs., Some wages are also "cost determined", as for instance, in Australia where until recently the Commonwealth basic wage was adjusted quarterly to changes in the C. Series price index. A realistic analysis of inflation processes should allow for both cost and demand influences in price and wage determination. (First paragraph of Precis.)